Life cycle assessment of aerogels: a critical review - Kara, Ilkay Turhan; Kiyak, Baris; Gunes, Neslihan Colak; Yucel, Sevil (SPRINGER, 2024)
Over the past decade, the increasing emphasis on sustainable material production has brought aerogel technology to the forefront of scientific and industrial research. Aerogels are known for their extraordinary properties, such as high porosity and low density, which make them suitable for a wide range of applications from thermal insulation in buildings to drug delivery systems. This review systematically investigates the sustainability of aerogel production by analyzing the environmental impacts identified in recent life cycle assessments (LCAs). It examines studies on aerogel production using different precursors, solvents, and energy-intensive production methods, especially drying techniques, providing a comprehensive analysis of the environmental footprints and highlighting several hotspots. The review particularly focuses on identifying the disparities in LCA methodologies and the results obtained, which are crucial for crafting a roadmap toward more sustainable aerogel production. The findings emphasize the need for standardized functional units and lifecycle phases that reflect the specific applications of aerogels, thus enabling more accurate comparisons and assessments. The review concludes with a discussion of the critical gaps in current LCA studies of aerogels. It also offers sustainability recommendations based on identified hotspots, advocating for improvements in aerogel production techniques that minimize environmental impacts, enhance material efficiency, and reduce waste. By addressing these gaps, this paper aims to foster a deeper understanding of aerogel sustainability and encourage the development of more environmentally friendly practices in aerogel production and application.
Keywords: Aerogel production; LCA; Environmental impacts; Sustainability; Precursors; Drying techniques; RICE HULL ASH; SILICA AEROGEL; FLY-ASH; SUSTAINABILITY ASSESSMENT; PHYSICAL-PROPERTIES; STARCH AEROGELS; HUSK ASH; ALGINATE; PERFORMANCE; COMPOSITES; Materials Science